A mathematical model of vibration signal for multistage wind turbine gearboxes with transmission path effect analysis. (January 2022) - Nie, Yanyan; Li, Fangyi; Wang, Liming; Li, Jianfeng; Sun, Mingshuai; Wang, Mengyao; Li, Jianyong
Highlights: A mathematical vibration model of multistage wind turbine gearboxes is proposed. Modulation sidebands in the vibration spectrum are explained based on the model. The equivalent transmission path functions in the multistage gearbox are proposed. The conclusions are validated based on data from 2.0MW wind turbine gearboxes. Abstract: The sensor-perceived vibration signals of multistage wind turbine gearboxes have more complex frequency features than that of single-stage gearboxes since there are more meshing vibration sources and more complicated transmission paths inside them, which lead to difficulties in condition monitoring and fault diagnosis. Aiming to understand the vibration frequency features of multistage wind turbine gearboxes, a mathematical vibration model of healthy wind turbine gearboxes is developed and the spectral structure of the model is deduced by adopting Fourier series analysis. In the vibration model, the time-varying transmission paths from all the meshing vibration sources to the fixed sensor are considered, and the equivalent transmission path functions of the time-varying transmission paths are proposed for the first time. The theoretical derivations are validated by both simulations and engineering tests using two cases of 2.0MW industrial wind turbine gearboxes. The findings in this work are not only applicable to the gearboxes studied in this paper, but also to other similar multistage gearboxes, which can provide a priori spectral structure for the multistage gearbox to assist its condition monitoring and fault diagnosis.